2013
DOI: 10.1519/jsc.0b013e31824e1711
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Three Different Endurance Tests in Professional Soccer Players

Abstract: The aims of this study were (a) to assess and correlate interval shuttle run test (ISRT) performance, maximum oxygen uptake (V[Combining Dot Above]O(2)max), running economy (RE), running velocity at the first rise in blood lactate concentrations above baseline (vLT) and running velocity at 4 mmol·L(-1) blood lactate concentration (v4) in professional soccer players and (b) to investigate whether a correlation exists between the respective results of time to exhaustion (T(lim)) from continuous and intermittent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 25 publications
2
26
0
2
Order By: Relevance
“…A recent study revealed a correlation between v2 and Yo-Yo test performance ( r =0.73 P =0.003) in female soccer players [16]. In contrast, no correlation was found between v2, v4 and v max and ISRT performance in male soccer players, confirming previous research [12]. These data may hypothetically show that the predominantly aerobic metabolism, as assessed here via the lactate threshold, is more important for intermittent running performance in female than in male soccer players.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…A recent study revealed a correlation between v2 and Yo-Yo test performance ( r =0.73 P =0.003) in female soccer players [16]. In contrast, no correlation was found between v2, v4 and v max and ISRT performance in male soccer players, confirming previous research [12]. These data may hypothetically show that the predominantly aerobic metabolism, as assessed here via the lactate threshold, is more important for intermittent running performance in female than in male soccer players.…”
Section: Discussionsupporting
confidence: 78%
“…The incremental test was performed on a dry 400 m outdoor allweather running track with running shoes as reported previously [12]. The track was marked every 50 m with pylons and an acoustic signal was used to control the running speed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All anthropometric and physical capacity tests were performed on one day during the pre-season preparation, where all players had attained a high-performance level. The tests were performed as previously described (28,29) and were conducted in the following order: (a) anthropometric measures, (b) speed and COD tests, (c) SJ and CMJ tests, (d) a bench press test, (e) four different core strength-endurance tests, and (f) an intermittent shuttle running test. Before testing, the duration of the summer break and pre-season preparation as well as number of training sessions were approximately the same for juniors (i.e., six weeks, six weeks, and 36 sessions, respectively) and adults (i.e., four weeks, four weeks, and 40 sessions, respectively).…”
Section: Experimental Designmentioning
confidence: 99%
“…Finally, for the intermittent endurance test, the players performed an interval shuttle run test (ISRT) (28). Thereby, the players ran 20 m shuttles at progressively increasing velocities controlled by audio signals from a computer.…”
Section: Intermittent Shuttle Running Testmentioning
confidence: 99%